2009
DOI: 10.3892/or_00000418
|View full text |Cite
|
Sign up to set email alerts
|

Detection of glypican-3-specific CTLs in chronic hepatitis and liver cirrhosis

Abstract: Abstract. Glypican-3 (GPC3) is one of carcinoembryonic antigens known to be overexpressed in hepatocellular carcinoma (HCC). It has been suggested that GPC3 may be related to the development of HCC in a background of chronic hepatitis (CH) and liver cirrhosis (LC). Therefore, in an attempt to establish an early diagnostic marker of HCC, we quantified the number of GPC3-specific CTLs in the peripheral blood of CH and LC patients. We selected CH and LC patients who were HCV-RNA (+) or HBs antigen (+) within 6 mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 25 publications
(35 reference statements)
0
9
0
Order By: Relevance
“…Although evidence of immune response to these two antigens in HCC patients has been demonstrated, eliciting antitumor immunity using these two antigens is still not robust. 18-21 One of the potential explanations is that the expression of these two proteins during embryogenesis may have caused immune tolerance in adults. However, it is still unclear how the host immunosurvillence mechanisms interact with HCC to allow tumor to grow.…”
Section: Introductionmentioning
confidence: 99%
“…Although evidence of immune response to these two antigens in HCC patients has been demonstrated, eliciting antitumor immunity using these two antigens is still not robust. 18-21 One of the potential explanations is that the expression of these two proteins during embryogenesis may have caused immune tolerance in adults. However, it is still unclear how the host immunosurvillence mechanisms interact with HCC to allow tumor to grow.…”
Section: Introductionmentioning
confidence: 99%
“…Hayashi et al, quantified the number of GPC3-specific CTLs in the peripheral blood of patients with either chronic hepatitis or liver cirrhosis [44]. They selected patients who were HCV-RNA (+) or HBs antigen (+) within 6 months prior to the study for which no HCC nodules were detected by radiologic imaging.…”
Section: Immunotherapeutic Gpc3 Vaccinementioning
confidence: 99%
“…We previously reported that 39% of HCC patients had detectable GPC3-specific CTLs by a direct ex vivo IFN-γ ELIsPOT assay (25). In this study, GPC3-specific CTLs were detectable before treatment in 11 of 27 patients (41%).…”
Section: Discussionmentioning
confidence: 60%